2020
DOI: 10.1007/s42001-020-00091-8
|View full text |Cite
|
Sign up to set email alerts
|

Influencing overseas Chinese by tweets: text-images as the key tactic of Chinese propaganda

Abstract: The literature on China’s social media foreign propaganda mostly focuses on text-format contents in English, which may miss the real target and the tool for analysis. In this article, we traced 1256 Twitter accounts echoing China government’s #USAVirus propaganda before and after Twitter removed state-linked operations on June 12, 2020. The 3567 tweets with #USAVirus we collected, albeit many written in English, 74% of them attached with a lengthy simplified Chinese text-image. Distribution of the post-creatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Therefore, the count of quotes from China's official Twitter data is more conducive to increasing the count of Tweets about China's carbon policy than simple retweets, which is more conducive to enhancing China's international image. In summary, China's official accounts Twitter data plays an important role in improving the world's positive views on China's carbon reduction policy, which is consistent with the intended role of the Chinese government's official Twitter accounts in promoting a positive national image as described in previous studies [58,70].…”
Section: Impact Of China's Official Twitter Accountssupporting
confidence: 87%
“…Therefore, the count of quotes from China's official Twitter data is more conducive to increasing the count of Tweets about China's carbon policy than simple retweets, which is more conducive to enhancing China's international image. In summary, China's official accounts Twitter data plays an important role in improving the world's positive views on China's carbon reduction policy, which is consistent with the intended role of the Chinese government's official Twitter accounts in promoting a positive national image as described in previous studies [58,70].…”
Section: Impact Of China's Official Twitter Accountssupporting
confidence: 87%
“…The first video was usually uploaded before noon, and the second was published around 5 pm. The time distributions are similar to those of previous coordinated behaviors of the Chinese cyber army on Twitter (A. H.-E. Wang et al 2020). Taken together, the publication times suggest that the videos were created by employees during working hours, not by amateurs after class or work.…”
Section: Finding 2: Evidence Of Potential China-related Coordinationsupporting
confidence: 75%
“…Recently, A. H.-E. Wang et al (2020) found that the text-image on Twitter was more important than the 140-word post in explaining the discourse of the Chinese cyber army as well as the criteria for censorship by Twitter. We also suggest that China may promote its propaganda through YouTube videos, not just words or text-images.…”
Section: Puppet Anchors In China's Information Operationsmentioning
confidence: 99%
“…Ferreira et al proposed the concept identification of weak learning algorithms and strong learning algorithms, and their equivalence problem, that is, whether it is possible to upgrade weak learning algorithms to strong learning algorithms [15]. Wang et al believe that parallel development on the spark platform has several very important benefits: first, the spark has a unified API, so it is very easy to develop applications; Second, the spark can perform different operations on the same data, and these different operations can be combined to obtain higher efficiency; ird, spark usually operates in memory and has high efficiency [16]. Patil and Deore put forward a circular data analysis model, which includes seven parts: data collection, storage, data cleaning, integration, data analysis, data presentation and visualization, and corresponding behaviors.…”
Section: Related Workmentioning
confidence: 99%